Gender Equality and Social Inclusion (GESI) for climate-smart water management practices: the case of Upper Awash River Basin of Wollo and Lower Awash River Basin of Afar in Ethiopia - Nigussie, Likimyelesh; Joshi, Deepa; Tsegaye, B.; Admasu, W.; Abate, N. (International Water Management Institute, 2024)
This research study on gender and water resources management, led by the International Water Management Institute (IWMI) and its partners in Ethiopia, was designed to collect primary and secondary data on how smallholder agricultural producer communities in selected catchments are impacted by and cope with climate change. Our focus was on exploring opportunities and barriers for designing and implementing gender-responsive and climate resilient water resources planning and management interventions that are contextually relevant. The research findings will be further translated into actionable recommendations for gender-responsive decision support tools for climate-smart water resources management. The study, informed by the Gender Empowerment Framework and a qualitative research methodology, analyzed soil and water conservation initiatives and small-scale irrigation (SSI) interventions in four districts of the Awash River Basin. These locations were the Kalu and Habru districts from the Upper Awash Catchment in Wollo, and the Ewa and Afambo districts from the Lower Awash Catchment in Afar. These four districts were chosen for their diversity of conservation initiatives and livelihoods. Data were collected from a total sample size of 309 individuals – 288 of whom were smallholder farmers (160 women and 128 men) and 21 were key informants from local government offices – by conducting 96 in-depth interviews, 24 focus group discussions and 21 key informant interviews. The data were analyzed to assess the gender dynamics of productivity, production and practices, and SSI practices, focusing on three key dimensions: resources, agency and institutions. The three key results and recommendations are as follows: